The Principles of Post-Operative Management and Rehabilitation of Patients Using the Single-Stage Implant Method - Ismatov Farrukh Aslidinovich; Mustafoev Abdullojon Abdurasulovich (Genius Journals, 2022)
Defects of the dentition (especially without preservation of the antagonists) lead to changes in the facial configuration, lower third height, deformation of the dentition, pathology of the temporomandibular joint (TMJ) and development of myofascial pain syndrome (prosopalgia), which aggravates the primary pathology. Occasionally, significant defects of the dentition are accompanied by habitual subluxation or dislocation of the temporomandibular joint. The absence even of single teeth leads to instability of the whole dentition, their displacement (Popov-Godon phenomenon), overloading of the periodontium of the remaining teeth, disturbance of the biomechanics of the whole dentoalveolar system and the occurrence of traumatic occlusal blocks. This results first in gingivitis, followed by bone destruction and the development of pathological pockets.
Keywords: radiography; odontometry; height of bone